PROBLEMATIKA PENANGANAN DAMPAK SOSIAL KEMASYARAKATAN DALAM RANGKA PENYEDIAAN TANAH UNTUK PEMBANGUNAN NASIONAL (STUDI PELAKSANAAN PEMBANGUNAN PUSAT PEMERINTAHAN KABUPATEN TANA TIDUNG) - JAYANTI, LITA FITRIANI (JURNAL AKTA YUDISIA, 2025)
This paper discusses the regulation of Social Impact Management (PDSK) in land acquisition for national development. Its legal basis derives from the Basic Agrarian Law of 1960 (UUPA) and Article 33 of the 1945 Constitution, further elaborated in Law No. 2/2012, Presidential Regulation No. 62/2018, Minister of Home Affairs Regulation No. 117/2018, Coordinating Minister for Economic Affairs Regulation No. 20/2020, and Minister of Agrarian Affairs/National Land Agency Regulation No. 6/2020. The core issue is not merely the release of land rights, but how to guarantee justice for affected communities, particularly through consultation, fair compensation, and the use of consignment mechanisms in cases of rejection. The case study in Tana Tidung Regency shows that the construction of a government center can only proceed with social legitimacy when accompanied by transparent and accountable PDSK. In conclusion, PDSK is an essential instrument to ensure that development runs smoothly without impoverishing communities and while respecting their rights.